Mammaglobin expression in tissue as a predictor of breast carcinoma aggressiveness - Milošević Bojan; Cvetković Aleksandar; Ninković Srđan; Marković Snežana; Mitrović Slobodanka; Stojanović Bojan; Radunović Aleksandar; Vulović Maja; Cvetković Danijela (Vojnosanitetski Pregled)
Background/Aim. Human mammaglobin is considered to be one of the most significant markers of hematogenous dissemination of breast carcinoma. This paper aimed to indicate the important role of peritumoral tissue as an active participant in the tumorigenesis process and the concentration/expression of mammaglobins in the peritumoral tissue as a significant prognostic factor. Methods. This research included 64 female patients with primary breast carcinoma during the five-year follow-up period. To determine the concentration of mammaglobin A in samples of carcinoma tissue and peritumoral tissue, Enzyme-linked immunosorbent assay (ELISA) test was used, and for the determination of relative gene expression of mammaglobin A, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used. Results. The concentration of mammaglobin A was increased in both the carcinoma tissue and peritumoral tissue with an increase in tumor size, number of affected lymph nodes, number of metastases, while relative expression of mammaglobin A was statistically significantly higher in carcinoma tissue than in peritumoral tissue, regardless of the tumor size, number of affected lymph nodes, number of metastases and tumor type. The concentration of mammaglobin A was higher in peritumoral tissue than in tissue of ductal carcinoma, while in the case of lobular carcinoma the concentration of mammaglobin A was higher in carcinoma tis-sue than in peritumoral tissue. Conclusion. Mammaglobin A concentration in peritumoral tissue higher than 0.6704221 ng/mL, and in carcinoma tissue higher than 0.5784426 ng/mL, as well as mammaglobin A relative gene expression in carcinoma tissue higher than 1.003, were determined as cut-off values. These values may identify patients who are at higher risk of metastatic disease, which would be treated with early radical adjuvant treatment.